Розрахункові дослідження пульсацій тиску в стенді для випробування гідроапаратів - Андренко, Павло Миколайович; Свинаренко, Максим Сергійович (Eastern-European Journal of Enterprise Technologies, 2010)
The comparative analysis of pulsations of pressure in the stand for tests of hydrodevices is lead at presence extinguisher pulsations of pressure with automatic fine tuning parameters and without it